PROFIL USAHA PETERNAKAN ITIK DI KABUPATEN BREBES (The Profile of Duck Business in Brebes Regency) - Migie Handayani; Agus Setiadi; Siwi Gayatri; Hery Setiyawan (JURNAL SOSIAL EKONOMI PETERNAKAN, 2013)
ABSTRAKPenelitian ini untuk mengetahui profil peternakan itik di Kabupaten Brebes. Metode penelitian menggunakan metode survey. Data primer penelitian berasal dari interview langsung dengan responden. Responden adalah anggota kelompok tani ternak (KTT) dipilih secara purposive random sampling. Analisis data secara deskriptif. Hasil penelitian menunjukkan bahwa rata-rata peternak sudah berpengalaman sebagai peternak itik selama 4,85 tahun, strain itik lokal bersal dari Tegal dan Cirebon. Hasil penelitian juga menunjukkan bahwa penyakit ND dan cholera adalah penyakit yang sering menjangkiti peternakan itik di Kabupaten Brebes. Harga produk telur itik dijual antara Rp 550,- sampai Rp 610,- dan rata-rata pendapatan peternak sebulan sebesar Rp 568.604,-.Kata kunci : profil, usaha peternakan itik.ABSTRACTThis research to know profile of effort ranch of duck in Brebes Regency. The method research by survey method. Collected data cover primary data and secondary data. Primary data obtained from responder pursuant to interview at society by using questionnaire. Research location reside in Brebes Regency representing potential duck livestock. Determining three Economic Enterprise (KTT) were exist in Brebes Regency by purposive random sampling. Each KTT taken by 10 farmer to be made as responder by random. Then the data ware analysed with descriptive qualitative, that is taking field data, analysing obtained data, then result of which is obtained to be concluded. The result of research indicate that mean experience of farming the responder 4,85 year. Duck strain are local duck which come from Tegal and Cirebon. Mean of amount of looked after counted 588. Ordinary disease attack are ND and cholera. Passed to feed are intact fish, dry rice, thorn fillet fish and bran. The eggs product to be sold to compiler merchant and some of processed theirself become briny egg. Egg price range from Rp 550,- until Rp 610,-. Earnings mean every month the responder breeder equal to Rp 568.604,-.Keyword : profile, effort ranch of duck